Bruce Nauman - Lissoni, Andrea 1970-; Serota, Nicholas 1946- (Tate Publishing, 2020)
Since the late 1960s Bruce Nauman has established a completely new understanding of contemporary art and has been acknowledged as one of the most relevant artists of the twentieth century. Both the last modern artist and - because of his ceaseless experimental approach to new media - the very first contemporary artist, Nauman has been noted for his landmark conceptual approach against which much contemporary art of today can be measured. Focusing in particular on his experiments with sound, the moving image and immersive installations, this book comprises texts on Nauman's video works of the 1980s and 1990s, as well as on his studio practice and more recent work, along with a conversation between the artist and Andrea Lissoni and Nicholas Serota.
Rückseite Titelblatt: ... on the occasion of the exhibition "Bruce Nauman", Tate Modern, London, 7 October 2020 - 21 February 2021; Stedelijk Museum, Amsterdam, 27 March - 15 August 2021; Pirelli HangarBicocca, Milan, 7 October 2021 - 20 February 2022
Keywords: Nauman, Bruce -- 1941-; Ausstellungskatalog -- Pirelli HangarBicocca -- 07.10.2021-20.02.2022 -- Mailand; Ausstellungskatalog -- Stedelijk Museum -- 27.03.2021-15.08.2021 -- Amsterdam; Ausstellungskatalog -- Tate Modern -- 07.10.2020-21.02.2021 -- London